A study of house officers in a teaching Hospital on knowledge, perception of skills and confidence level in performing CPR - Ismail Mohd Saiboon,; Noraliza Mohd Ariffin,; Teodoro Javier Herbosa,; Nariman Singmamae,; Ahmad Khaldun Ismail,; Azhana Hassan,; Shamsuriani Md Jamal,; Ho, Siew Eng (Penerbit UKM, 2007)
Cardio-pulmonary Resuscitation (CPR) is important and should be mastered by House Officers (HO). House officers who have just completed their studies are assigned to acute medical and surgical wards. If a patient in the ward has a cardiac arrest (CA), these doctors are usually the first to attend. Therefore an HO must be confident with CPR skills. They must be competent in performing CPR. The authors assessed 26 new HOs from Universiti Kebangsaan Malaysia Hospital (HUKM) with respect to their self-perception about CPR skills, confidence level in performing CPR and knowledge in performing CPR.Knowledge was assessed by a questionnaire. We found that 16 of 26 (61.5%) assessed themselves to have inadequate knowledge and 46.2% had no confidence in performing CPR. The mean score of the written test was 5.7 ± 1.8. Seven out of 26 (27.0%) HOs had incorrect hand placement position for CPR. Only 4 and 9 out of 26 HOs had their sternal paddle and cardiac apex paddle positions correctly placed respectively. In conclusion, knowledge, perception of skills and confidence levels of HOs on CPR are inadequate and need further assessment and improvement. Medical schools need to review their CPR curriculum in order to prepare HOs adequately to work in emergency situations